2007
DOI: 10.1086/509496
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Quantum Corrections to Screening in Thermonuclear Fusion

Abstract: We develop a series expansion of the plasma screening length away from the classical limit in powers ofh 2 . It is shown that the leading order quantum correction increases the screening length in solar conditions by approximately 2% while it decreases the fusion rate by approximately 0.34%.We also calculate the next higher order quantum correction which turns out to be approximately 0.05%.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…One of the first studies that, on a microscopic basis, demonstrated deviations from the D-H factor was carried out by Johnson et al (1992;see also Shaviv 2004;Shaviv & Shaviv 2000, 2002Chitanvis 2007). The different approaches mentioned so far are based on the assumption that electrons are distributed in space according to a Boltzmann factor.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first studies that, on a microscopic basis, demonstrated deviations from the D-H factor was carried out by Johnson et al (1992;see also Shaviv 2004;Shaviv & Shaviv 2000, 2002Chitanvis 2007). The different approaches mentioned so far are based on the assumption that electrons are distributed in space according to a Boltzmann factor.…”
Section: Introductionmentioning
confidence: 99%
“…The use of CD 2 solid-state targets can enhance the neutron production. In addition, the use of CD 2 solid-state targets can also lead to direct measurements of the reaction rates at low temperatures and great enhancement on the plasma screening comparing to the case of D 2 gas jet targets, offering the possibility to access to these so far unsolved issues in the field of astrophysics [18][19][20][21][22][23][24][25][26][27][28][29][30].We first study the neutron events as functions of plasma temperature adopting a general spherical plasma model, and calculate the neutron spectra. Then we model the plasma formation by the scaling law method for D 2 gas jet targets, and the particle in cell (PIC) method for CD 2 solid-state targets.…”
mentioning
confidence: 99%
“…The use of CD 2 solid-state targets can enhance the neutron production. In addition, the use of CD 2 solid-state targets can also lead to direct measurements of the reaction rates at low temperatures and great enhancement on the plasma screening comparing to the case of D 2 gas jet targets, offering the possibility to access to these so far unsolved issues in the field of astrophysics [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma screening effect for thermonuclear reactions has continued to be intensively studied theoretically in the past decades [8,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], and it could not remain free of controversy given that experimental tests are missing so far [1,7,27,28]. Theoretical models focus mostly on classical plasma models [8,[11][12][13][14][15], while quantum plasma models only address the weak screening regime and have shown good agreement with the classical weak screening [16,[19][20][21]. Hints on the important role of quantum effects come from the atomic counterpart of plasmas screening, the plasma-induced ionization potential depression (IPD).…”
mentioning
confidence: 99%